Comparative analysis of intermittent and continuous energy restriction in obesity management - Görücü, Dilan Dalgıç; Yeşil, Esen; Özdemir, Merve; Köse, Beril (International Journal of Public Health Science (IJPHS), 2024)
An alternative to continuous energy restriction in the medical nutrition treatment of obesity, which has come to the fore in recent times, is called intermittent fasting. The aim of this study is to compare the effects of intermittent energy restriction (IER) and continuous energy restriction (CER) practices on body composition and anthropometric measurements in overweight and first-degree obese individuals. The comparison study was conducted on 34 people aged 19-64 between April and September 2022. They had no health problems, and applied to a private institution providing nutrition consultancy. In the study, the participants were divided into two groups and were asked to maintain the IER or CER diet type for six weeks. When the participants in the two diet types were compared in terms of parameters of anthropometric measurements, body compositions, blood pressure measurements, and initial and final measurements of abdominal fat analysis, no statistically significant difference was found (pα, pβ>0.05). The mean weight loss of the participants in the IER and CER groups was 3.95±1.94 kg and 4.09±1.48 kg, respectively. The weight loss of the participants in the two diet groups was similar. The long-term efficacy and safety of time-restricted feeding in weight loss is still unclear. More comprehensive research is needed on this subject.